Molecular insights into the electric double-layer structure at a polymer electrolyte-electrode interface. (1st April 2023) - Asha, Aysha Siddika; Iroegbu, Justice Nkemakolam; Visayas, Benjoe Rey B.; Mayes, Maricris; Shen, Caiwei
Abstract: Polymer electrolyte-based electric double-layer supercapacitors (EDLCs) have been increasingly studied for flexible, wearable, and multifunctional energy storage applications. Although the phenomenon that electrode materials present significantly lower EDL capacitances in polymer electrolytes than in liquid electrolytes has been widely observed, it has not been well studied and explained. Here we present the molecular dynamics simulation of a representative polymer electrolyte-based EDLC to reveal the atomic structure of such a polymer electrolyte-electrode interface for the first time. The polymer electrolyte composed of polyethylene oxide and lithium perchlorate is simulated between graphene electrodes and compared with an aqueous electrolyte-based system with the same lithium salt. We find that the polymer-based system shows unique EDL structures in the inner and outer Helmholtz layers that are not seen in the aqueous one. Statistical analyses along with ab initio calculations show that the disparities mainly come from the different interaction strengths between ions, polymer or water molecules, and graphene electrodes. Despite these disparities, the intrinsic interfacial capacitances calculated from various simulated charge states of different EDLCs show very close values. Combined with experimental measurements, we conclude that the reduced capacitances with polymer electrolytes reported in the literature come from the poor interface between electrode and electrolyte, which can be significantly improved through proper thermal treatments.